EFFECT OF PLATELET RICH PLASMA ON PROLIFERATION OF ENDOTHELIAL PROGENITOR CELL (EPC) OF STABLE CORONARY ARTERY DISEASE PATIENT - Ronald Rendy Hehanusa; Andrianto Andrianto; Budi S Pikir (Jurnal Kardiologi Indonesia, 2019)
ABSTRACT Effect of Platelet Rich Plasma (PRP) on Proliferation of Endothelial Progenitor Cell (EPC) of Stable Coronary Artery Disease Patient Ronald R Hehanusa, Andrianto, Budi S Pikir Background : Endothelial Progenitor Cell (EPC) is the progenitor of endothelial cell which has important role in regulation of vascular wall integrity and homeostasis, to protect vessels from inflamation and thrombosis, that leads into pathogenesis of coronary artery disease. Growth factors proven has important role to stimulate transduction signal in the process of proliferation of EPC. Platelet Rich Plasma (PRP) contains variety of growth factors, wellknown role in homeostasis and wound healing process. Therefore, this study was conducted to analyze the effect of PRP on proliferation of EPC of Stable Coronary Artery Disease (SCAD) patient. Objective : To analyze the effect of Platelet Rich Plasma (PRP) on the proliferation of Endothelial Progenitor Cell (EPC) from peripheral blood of patient with SCAD Methods : This is an in vitro, true experimental, post-test only control group design. The mononuclear cells were isolated from peripheral blood of SCAD patient and cultured in M-199 medium. EPC divided into 3 groups, which received Platelet Rich Plasma (PRP), Platelet Poor Plasma (PPP), and control. After 14 days of incubation, immunocytochemical examination was performed, EPC which marked with CD34, FITC labeled,was counted using immunofluoroscence microscope. Data analysis using ANOVA test. Result : Cell counting showed significant increase of EPC proliferation in PRP group compared to PPP group (1.052 ± 0.16 vs 0.762 ± 0.19, p = 0.003), and control group as well (1.052 ± 0.16 vs 0.068 ± 0.05, p = 0.000). EPC proliferation in PPP group also increase significantly compared to control group (0.762 ± 0.19 vs 0.068 ± 0.05, p = 0.000). Conclusion : Platelet Rich Plasma (PRP) increase EPC proliferation significantly from peripheral blood of SCAD patient. Keywords : EPC proliferation, PRP, SCAD